CRITICAL REVIEW OF THE ROLE OF ARTIFICIAL INTELLIGENCE IN ISLAMIC EDUCATION MANAGEMENT IN MADRASAH - Ilmi, Khasanah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Research in Artificial Intelligence (AI) assesses its impact on educational management, focusing on Madrasah Head roles. This qualitative approach employs library studies as its research design, effectively achieving its goals. AI encompasses human-like intelligence, including cognitive abilities, learning, adaptability, and decision-making. However, not all AI can fulfill Madrasah Head responsibilities, such as managing, educating, administrating, leading, innovating, motivating, and mediating, as it can't encompass humanism and exemplarity. Although AI is widely adopted in various fields, it initially took the form of computers and evolved into web-based educational systems, humanoid robots, and chatbots for instructor tasks. While these platforms enhance administrative functions and teaching quality, they lack consideration for human challenges in Madrasah. They operate based on programmed settings and can't foster creativity, which is essential in education. The spirit of educational management is rooted in communication, interaction, and a persuasive approach among Madrasah Heads, teachers, and staff, particularly in Islamic institutions where exemplary leadership is paramount. Despite rapid technological advancements, the irreplaceable role of Madrasah Heads remains essential, as they embody values and qualities that technology or AI cannot replicate